Classification of Eucalyptus urograndis hybrids under different water availability based on biometric traits - Silva, Claudia D. [UNESP]; Nascimento, Janiele S.; Scarpinati, Edmar A.; Paula, Rinaldo C. [UNESP] (Inst Nacional Investigacion Technologia Agraria Alimentaria, 2014)
Aim of study: The eucalyptus grows rapidly and is well suitable to edaphic and bioclimatic conditions in several regions of of the world. The aim of this study was to assess the performance of Eucalyptus urograndis hybrids grown under different water availability conditions.Area of study: The study was performed in south-eastern of BrazilMaterial and methods: We evaluated five commercial hybrids cultivated in pots with the substrate maintained at 65, 50, 35 and 20% maximum water retention capacity. The evaluation was based on the following characteristics: total height (cm), diameter (mm), number of leaves, leaf area (dm(2)), and dry weight (g plant(-1)) of leaf, stem +branches, root, shoot and total and root/shoot ratio.Main results: All the characteristics evaluated were adversely affected by reduced availability of water in the substrate. The hybrids assessed performed differently in terms of biometric characteristics, irrespective of water availability. Water deficit resulted in a greater reduction in the dry weight production compared to number of leaves, diameter and height. Hybrids H2 and H5 have favorable traits for tolerating drought. The hybrid H2 shows a stronger slowdown in growth as soil moisture levels drop, although its growth rate is low, and H5 increases the root/shoot ratio but maintains growth in terms of height, even under drought conditions.Research highlights: The results obtained in our experiment show that productive hybrids sensitive to drought could also perform better under water deficit conditions, maintaining satisfactory growth despite significant drops in these characteristics.
Keywords: Eucalyptus urograndis; water deficit; drought tolerance